The Hahn-Banach Extension Theorem for Fuzzy Normed Spaces Revisited - Carmen Alegre; Salvador Romaguera (Abstract and Applied Analysis)
This paper deals with fuzzy normed spaces in the sense of Cheng and Mordeson. We characterize fuzzy norms in terms of ascending and separating families of seminorms and prove an extension theorem for continuous linear functionals on a fuzzy normed space. Our result generalizes the classical Hahn-Banach extension theorem for normed spaces.